Development of synthetic time histories at bedrock for Kuala Lumpur - Adnan, Azlan; Hendriyawan, Hendriyawan; Marto, Aminaton; Irsyam, Masyhur (2006)
Acceleration Time-histories of earthquake ground motions are required for analyzing the structural performances and response of soil deposits under seismic loading. Selection of appropriate time-histories for specific geological and seismological conditions plays an important role for obtaining accurate results. Due to lack of representative strong motion data recorded in Malaysia, synthetic ground motions were generated in the frequency domain by using spectral matching analysis and random vibration theory. The uniform hazard spectra (UHS), which are required for developing synthetic time histories, were obtained from probabilistic seismic hazard analysis using attenuation relationships for response spectrum. In this study, two UHS were developed for 10% and 2% Probability Exceedance (PE) in design time period of 50 year or correspond to return period of approximately 500 and 2,500 years, respectively. Two time histories for each hazard level were generated in this study, which represent the most likely and mean contribution magnitude-distance combinations. Finally, the time histories were applied in using 1-dimensional shear wave propagation analysis to obtain peak acceleration and amplification factor at the surface of Kuala Lumpur. The results indicate that the selection of appropriate time histories is one of the most critical in ground response analysis. The accelerations at the surface could be different up to about 35%.